Vasoactive intestinal peptide increases apoptosis of hepatocellular carcinoma by inhibiting the cAMP/Bcl‐xL pathway. Issue 1 (4th December 2018) - Hara, Masaki; Takeba, Yuko; Iiri, Taroh; Ohta, Yuki; Ootaki, Masanori; Watanabe, Minoru; Watanabe, Daiki; Koizumi, Satoshi; Otsubo, Takehito; Matsumoto, Naoki
Abstract : Vasoactive intestinal peptide (VIP) is a modulator of inflammatory responses. VIP receptors are expressed in several tumor types, such as colorectal carcinoma. The study described herein was conducted to confirm the presence of VIP and its receptors (VPAC1 and VPAC2) in surgically resected hepatocellular carcinoma (HCC) tissues and in the HCC cell line Huh7. The mechanism responsible for apoptosis of HCC cells was then examined because VIP treatment (10 −10  M) significantly suppressed proliferation of Huh7 cells. In examining apoptosis‐related proteins, we found caspase‐3 to be significantly increased and Bcl‐xL and cyclic AMP (cAMP) response element‐binding protein (CREB) to be significantly decreased in Huh7 cells cultured with VIP. Furthermore, the CREB level and phosphorylation were reduced. These effects were reversed by the addition of VIP receptor antagonist or cAMP antagonist Rp‐cAMPS. Pretreatment with cAMP analogue blocked the increased apoptosis, suggesting that VIP induces apoptosis via a PKA‐independent signaling mechanism. Our data indicate that VIP prevents the progression of HCC by apoptosis through the cAMP/Bcl‐xL pathway. Abstract : Immunohistochemical staining for VIP, VPAC1 and VPAC2 in non‐HPV‐B‐related HCC, non‐HPV‐C‐related HCC and Huh7 cells.